PERAN BAZNAS KOTA SAMARINDA DALAM MENINGKATKAN EKONOMI KAUM DUAFA - Khoirul Fathoni (Jurnal Riset Inossa, 2021)
The purpose of this study is to describe the role of the Samarinda City National Amil Zakat Agency (BAZNAS) in improving the economy of the poor during the Covid-19 pandemic season. This type of research is qualitative using case studies. Research data in the form of zakat management by BAZNAS Samarinda City obtained through online media such as Tribunkaltim.co.id, newspaper article Samarinda City Communication and Information Service, and Samarinda City BAZNAS. Researchers also explore data through recent studies that discuss the Samarinda City BAZNAS. Researchers document the data of BAZNAS Samarinda City in online media and e-journals. Documented data is presented systematically and accurately accompanied by valid sources. Meanwhile, data analysis was carried out by data reduction, data presentation, and data interpretation. The results of the study show that BAZNAS Samarinda City has carried out four strategies in improving the economy of the poor during the Covid-19 pandemic season as follows; 1) giving 4000 food packages with an estimated value of Rp. 500,000,000; 2) carry out the “pick up zakat at home” program; 3) cooperate with BAZNAS of the East Kalimantan Provincial Government in implementing the Zakat Community Development program; 4) offers Qard al-Ḥasan management in financing small and medium enterprises. The four strategies carried out by BAZNAS in Samarinda City were very appropriate and in accordance with the conditions at that time.